Effect of polyurethane/nanosilica composite coating on water resistance of paper substrate - Ching, K.S.; Ching, Yern Chee; Ng, C.A.; Ishenny, N.; Beg, M.T.H. (Taylor & Francis, 2014)
The effect of nanosilica particles on the water resistance of a polyurethane/nanosilica composite coated paper substrate was investigated. The polyurethane/nanosilica composite coating was prepared by dispersing nanosilica powder into solvent-based polyurethane using high mechanical stirring force. Paper substrate was coated with polyurethane/nanosilica composite using a Rod Mayer technique. Various compositions of polyurethane/nanosilica composite coatings on paper substrate were prepared. The total thickness of the paper coated with polyurethane/nanosilica composite was 0.3 mm. The field emission scanning electron microscopy images indicated that the presence of nanosilica has improved the surface roughness and porosity of paper substrate. The addition of nanosilica in polyurethane coating had increased the water resistance ability of the coated paper. It was demonstrated that polyurethane/nanosilica-6% shows better water resistance and exhibits better thermal stability than the nanocomposites with lower nanosilica loading. Fourier transform infrared spectroscopy result shows that there was no chemical reaction between nanosilica and polyurethane.